2023
DOI: 10.3390/cells12172187
|View full text |Cite
|
Sign up to set email alerts
|

MT1-MMP as a Key Regulator of Metastasis

Noritaka Tanaka,
Takeharu Sakamoto

Abstract: Membrane type1-matrix metalloproteinase (MT1-MMP) is a member of metalloproteinases that is tethered to the transmembrane. Its major function in cancer progression is to directly degrade the extracellular matrix components, which are mainly type I–III collagen or indirectly type IV collagen through the activation of MMP-2 with a cooperative function of the tissue inhibitor of metalloproteinase-2 (TIMP-2). MT1-MMP is expressed as an inactive form (zymogen) within the endoplasmic reticulum (ER) and receives trun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 121 publications
0
6
0
Order By: Relevance
“…ARF6 activity and its effectors JIP3 and JIP4 have been associated with MDA-MB-231 cell invasion through invadopodia-mediated mechanisms ( Marchesin et al, 2015 ). In particular, the authors found that the binding of active ARF6 to JIP3/JIP4 regulates the trafficking and exocytosis of MT1-MMP, a key regulator of invadopodia function ( Tanaka and Sakamoto, 2023 ). Furthermore, this study showed that the regulation of MT1-MMP trafficking occurs via the recruitment of motor proteins (dynactin-dynein and kinesin-1) by JIP3/JIP4 ( Marchesin et al, 2015 ).…”
Section: Endocytosis/recyclingmentioning
confidence: 99%
“…ARF6 activity and its effectors JIP3 and JIP4 have been associated with MDA-MB-231 cell invasion through invadopodia-mediated mechanisms ( Marchesin et al, 2015 ). In particular, the authors found that the binding of active ARF6 to JIP3/JIP4 regulates the trafficking and exocytosis of MT1-MMP, a key regulator of invadopodia function ( Tanaka and Sakamoto, 2023 ). Furthermore, this study showed that the regulation of MT1-MMP trafficking occurs via the recruitment of motor proteins (dynactin-dynein and kinesin-1) by JIP3/JIP4 ( Marchesin et al, 2015 ).…”
Section: Endocytosis/recyclingmentioning
confidence: 99%
“…The molecular mechanism underlying the initiation and sustenance the metastasis of tumor is intricate ( Tanaka and Sakamoto, 2023 ). The mechanism encompasses the establishment of a tumor microenvironment, the process of vascular remodeling, the acquisition of tumor cell invasiveness, and the reduction in tumor cell consumption ( Figure 3 ).…”
Section: Mechanisms Of Malignant Tumor Metastasismentioning
confidence: 99%
“…The importance of MT1-MMP in tumor metastasis has increased significantly in recent years [57]. Not only the degradation of collagen type 1-3 is important, but also the involvement of the enzyme in the migration and invasion of tumor cells has raised hopes for a successful therapy with specific inhibitors [57].…”
Section: Correlation Of Serum/endocervical Mucus Levels Of Mt1-mmp Wi...mentioning
confidence: 99%
“…The importance of MT1-MMP in tumor metastasis has increased significantly in recent years [57]. Not only the degradation of collagen type 1-3 is important, but also the involvement of the enzyme in the migration and invasion of tumor cells has raised hopes for a successful therapy with specific inhibitors [57]. Thus, our observation of an increased abundance of MT1-MMP, especially in adenomyosis, might be interesting for the development of future therapies against the disease.…”
Section: Correlation Of Serum/endocervical Mucus Levels Of Mt1-mmp Wi...mentioning
confidence: 99%